The circular economy between desiderate and realities - Laurențiu Tăchiciu (Amfiteatru Economic Journal, 2018)
By a "Quantitative Approach to Circular Economy in the OECD Countries " researchers use cluster analysis, correlation analysis and path analysis to uncover significant links and dependencies between economic growth, research-development and education on one side and the recycling rate on the other. Attempting an "Assessment of the Circular Economy's Impact in the EU Economic Growth ", other authors use time series data panel regressions to measure the impact of waste recycling rate on the resource productivity, confirming the hypothesis that recycling contributes to increasing resources productivity and thus to higher economic growth rates. [...]they found a negative relationship between the real GDP growth rate and the number of patents related to recycling and secondary raw materials, which reveals that innovation is motivated predominantly by environment protection objectives, neglecting the concomitant goal of increasing resources' productivity.
Keywords: 330